2023
DOI: 10.1002/chem.202300162
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Dispersibility of TiO2 Nanoparticles in Less Polar Solvents: Role of Ligand Tail Structures (Chem. Eur. J. 9/2023)

Abstract: The cover feature shows a schematic impression of our study on the dispersibility of TiO2 nanoparticles in less polar solvents. For ligand tail structures, there is a huge gap between saturated stearyl groups (depicted as waxes) and unsaturated oleyl groups (depicted as olives), even though there is very little difference in their molecular structures. In this study, we have synthesized two different ligands to bridge shores that are close yet far apart. More information can be found in the Research Article by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent detailed studies of organic ligands have revealed that a slight difference in the molecular structure of aliphatic ligands signicantly affects the dispersibility of the NCs. [10][11][12][13] Moreover, it has also been reported that the dispersibility and emission properties of NCs are altered by changing the primary, secondary, and tertiary structures of the phosphonic acids and thiols. 14 However, there are few examples that reveal the effect of the molecular structure of alkyl ligands on the excited-state dynamics of NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent detailed studies of organic ligands have revealed that a slight difference in the molecular structure of aliphatic ligands signicantly affects the dispersibility of the NCs. [10][11][12][13] Moreover, it has also been reported that the dispersibility and emission properties of NCs are altered by changing the primary, secondary, and tertiary structures of the phosphonic acids and thiols. 14 However, there are few examples that reveal the effect of the molecular structure of alkyl ligands on the excited-state dynamics of NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Even with ligands with the same molecular formula, slight differences in molecular structure can significantly change the dispersibility of nanoparticles modified with organic ligands. [23,[36][37][38] Therefore, it is important to understand which molecular structures of amphiphilic ligands are able to disperse nanoparticles in a variety of solvents for materials applications. Described herein are the results of structurefunction relationship studies of amphiphilic ligands designed to assess their ability to disperse nanoparticles in various solvents.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of the arrangement or the order of individual chains on the dispersibility in various solvents has not been examined systematically. Even with ligands with the same molecular formula, slight differences in molecular structure can significantly change the dispersibility of nanoparticles modified with organic ligands [23,36–38] . Therefore, it is important to understand which molecular structures of amphiphilic ligands are able to disperse nanoparticles in a variety of solvents for materials applications.…”
Section: Introductionmentioning
confidence: 99%